2014
DOI: 10.1038/nrcardio.2014.104
|View full text |Cite
|
Sign up to set email alerts
|

World Heart Federation expert consensus statement on antiplatelet therapy in East Asian patients with ACS or undergoing PCI

Abstract: | Guideline recommendations on the use of dual antiplatelet therapy (DAPT) in patients with acute coronary syndromes and in those undergoing percutaneous coronary intervention (PCI) have been formulated by both the ACC/AHA and the ESC. These recommendations are based primarily on large, phase III, randomized, controlled trials of the P2Y 12 inhibitors clopidogrel, prasugrel, and ticagrelor. However, few East Asian patients have been included in the trials to assess the use of these agents, particularly the new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
204
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 292 publications
(209 citation statements)
references
References 72 publications
3
204
2
Order By: Relevance
“…27 Genetic polymorphisms might partially account for the underlying mechanism of differing bleeding risk with ethnicity. 28 In addition, we found that the CRUSADE and ACTION risk scores had greater predictive value for major bleeding than the ACUITY-HORIZONS risk model.…”
Section: Discussionmentioning
confidence: 99%
“…27 Genetic polymorphisms might partially account for the underlying mechanism of differing bleeding risk with ethnicity. 28 In addition, we found that the CRUSADE and ACTION risk scores had greater predictive value for major bleeding than the ACUITY-HORIZONS risk model.…”
Section: Discussionmentioning
confidence: 99%
“…East Asian patients, despite a higher prevalence of clopidogrel resistance, seem to have a lower rate of ischemic events after DES implantation than Western patients, suggesting ethnic differences in the response to DAPT. 53 The maintenance dose of P2Y12 receptor blockers was determined from clinical trials conducted mostly in Caucasian populations. East Asians may require a lower dose of P2Y12 receptor blockers for similar protection from ischemic events.…”
Section: Ethnic Differencesmentioning
confidence: 99%
“…14, 15 Age and body weight may also differ on average from Caucasian populations, knowing that in the FEATHER trial 16 5 mg prasugrel in low body weight patients provided a similar level of platelet inhibition to 10 mg prasugrel in higher body weight patients. The Asian population also displays a higher PD response to prasugrel and ticagrelor with higher exposure to the active metabolite than do Caucasians, 17 suggesting that these drugs are not suitable at the standard dose regimens.…”
mentioning
confidence: 99%